The unexpected American origins of sexology and sexual science: Elizabeth Osgood Goodrich Willard, Orson Squire Fowler, and the scientification of sex. (February 2021) - Kahan, Benjamin
In spite of the fact that the term 'sexology' was popularized in the United States by Elizabeth Osgood Goodrich Willard and that the term 'sexual science'—which is usually attributed to Iwan Bloch as 'Sexualwissenschaft'—was actually coined by the American phrenologist Orson Squire Fowler in 1852, the archives of American sexology have received scant attention in the period prior to Alfred Kinsey. In my article, I explore the role of Transcendentalism and phrenology in the production and development of American sexology and sexual science. In particular, I argue that shifting the origins of sexology and sexual science away from Karl Heinrich Ulrichs and Karl-Maria Kertbeny and the more familiar narratives of the German invention of sexuality furnishes a radically different account of early sexology and sexual science. Rather than the unevenly homophilic sympathies of early German activists, their American counterparts promote marital, reproductive, loving sex and vilify prostitution, polygamy, masturbation, contraception, sex for pleasure, and, if they think to mention it, sodomy. In addition to this less progressive story, however, I argue that early American sexologists provide the first theories of gender and help to provide a fuller description of the politics of sexology and sexual science.